Detection of antimicrobial-resistant gram-negative bacteria in hospital effluents and in the sewage treatment station of Goiânia, Brazil - Batista Resende, Aline Cristina; Braz dos Santos, Daniela; Rodrigues do Carmo Filho, José; de Bastos Ascenso Soares, Renata; Rodrigues Montalvão, Edlaine (O Mundo da Saúde, 2009)
The emergence of antimicrobial-resistant genes and the indiscriminate use of antibiotics contribute to the dissemination of resistant pathogens in the environment. The objective of the present study was to isolate Pseudomonas aeruginosa, Acinetobacter spp., Klebsiella pneumoniae and Escherichia coli from the sewage effluents of 10 hospitals located in Goiânia, Brazil, and from the sewage treatment station of the city, to determine their susceptibility profile and investigate their resistance mechanisms. The isolates from water samples were identified by biochemical tests and confirmed using API 20E (BioMerieux). Susceptibility profiling was performed by disc diffusion in accordance with the methodology established by the National Committee for Clinical Laboratory Standards. Extended-spectrum β-lactamase (ESBL) detection was carried out by the disk approximation method using phenotypic tests. Sixty-seven microorganisms were isolated and identified, including E. coli 10 (14,92%), K. pneumoniae 10 (14,92%), P. aeruginosa 3 (4,47%) and A. baumannii 1 (1,49%). Of the E. coli strains, 100% were resistant to aztreonam, 40% to ampicillin, 30% to piperacillin, 20% to ciprofloxacin and 10% to gentamicin. None of the bacterial strains produced ESBL or carbapenems. Of the P. aeruginosa strains, 100% were resistant to ampicillin-sulbactam, while 100% had intermediate resistance to gentamicin. Strains of K. pneumoniae were resistant to ampicillin (70%) and to piperacillin (20%); additionally, 50% showed intermediate resistance to piperacillin. Total resistance was not found in any of the isolates of A. baumannii, which showed intermediate resistance to aztreonam and ceftriaxone. Overall, resistance rates were low in the isolates of E. coli, P. aeruginosa, K. pneumoniae and A. baumannii.